5.3A/400V normally‐off AlGaN/GaN‐on‐Si MOS‐HEMT with high threshold voltage and large gate swing. Issue 3 (1st January 2013) - Dong, Zhihua; Tan, Shuxin; Cai, Yong; Chen, Hongwei; Liu, Shenghou; Xu, Jicheng; Xue, Lu; Yu, Guohao; Wang, Yue; Zhao, Desheng; Hou, Keyu; Chen, Kevin J.; et al.
Abstract : Normally‐off AlGaN/GaN metal‐oxide‐semiconductor high electron mobility transistors (MOS‐HEMTs) on Si substrate were fabricated with the fluorine‐based treatment technique. By employing a 20nm‐thick Al2 O3 gate dielectric deposited by atomic layer deposition, the fabricated MOS‐HEMT exhibits a large positive threshold voltage of + 3.5V, a maximum gate input voltage of 15V, a maximum saturate drain current of 5.3A and an off‐state breakdown voltage of 402V. The high threshold voltage and the large input voltage swing is expected to improve the electromagnetic interference immunity and safety of AlGaN/GaN MOS‐HEMT power switches.